2017
DOI: 10.1177/2325967117712944
|View full text |Cite
|
Sign up to set email alerts
|

Semitendinosus Tendon for ACL Reconstruction: Regrowth and Mechanical Property Recovery

Abstract: Background:Semitendinosus/gracilis (STG) tendon autograft has been used effectively for restoring knee stability after anterior cruciate ligament (ACL) rupture. Though ACL reconstruction with STG autograft is an effective surgical technique for return to sports, short-term hamstring strength asymmetries exist after surgery. Although imaging evidence has demonstrated regrowth and reorganization of the semitendinosus (ST) tendon, no studies show whether the regrowth is associated with residual muscle function. C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
36
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 45 publications
(43 citation statements)
references
References 26 publications
2
36
0
5
Order By: Relevance
“…28 Suydam et al 28 demonstrated that less than 50% of the visco-elastic properties of the ST tendon had recovered by 12 months postoperatively, suggesting a reduced capacity to transmit muscle force across the joint. 28 An analysis of rRFD, an unbiased measure of rapid force ability, showed no difference between limb conditions. This suggests that differences in RFD ability are attributable to the between-limb absolute strength differences.…”
Section: Discussionmentioning
confidence: 99%
“…28 Suydam et al 28 demonstrated that less than 50% of the visco-elastic properties of the ST tendon had recovered by 12 months postoperatively, suggesting a reduced capacity to transmit muscle force across the joint. 28 An analysis of rRFD, an unbiased measure of rapid force ability, showed no difference between limb conditions. This suggests that differences in RFD ability are attributable to the between-limb absolute strength differences.…”
Section: Discussionmentioning
confidence: 99%
“…Tendon regeneration has been postulated to occur from an extrasynovial hematoma in the harvested tendon canal because hematoma acts as a scaffold for fibroblasts to invade and promote the mechanism for collagen production and tendon regeneration 13). Recently, Suydam et al25) demonstrated ST regeneration and recovery of functional biomechanical properties including shear elastic and viscous moduli with time using imaging and elastography data after ST-G harvesting. They demonstrated that the elastic modulus of the regenerated ST potentially transmitted muscle force across the joint and restored ST function.…”
Section: Discussionmentioning
confidence: 99%
“…Rehabilitation clinicians should therefore monitor donor-site pain when the patient performs quadriceps strengthening exercises. After ACLR with hamstring grafts, the mechanical properties of the neo tendons may eventually recover with time [78]. To allow for healing, heavy resistance hamstring strengthening exercises are usually delayed for a period postoperatively [75], but there is no consensus on the optimal time frame for initiation of heavy resistance hamstring exercises.…”
Section: Introductionmentioning
confidence: 99%